Management of long-term cryptococcal meningitis neoformans in a surviving patient: A case report - Hu, Shijun; Liu, Tao; Huang, Shixiong; Liang, Hui (Frontiers in Medicine, 2022)
Cryptococcal meningitis is a common fungal infection of the central nervous system with high mortality and disability rates. A prominent clinical manifestation is persistent and severe cranial hypertension, which is one of the most critical outcome determinants in patients with cryptococcal meningoencephalitis. Herein, we report and discuss a case of cryptococcal meningitis treated by an inadequate course of medical therapy and placement of a ventriculoperitoneal shunt in a patient who survived for more than 10 years.